Impact Of COVID-19 On Profitability of Banking Sectors In CEE - Pawel NIEDZIOLKA (Communications of International Proceedings, 2021)
The aim of the paper is to identify the CEE banking sectors with the lowest and the highest resilience to pandemic crisis. Resilience was examined using the PLR measure that reflects the scale of the loss of profitability of respective banking sectors between the end of 2019 and 30 September 2020. Data on 13 Central and Eastern European economies published by the European Central Bank were taken into account. The results obtained indicate that the Slovenian banking sector (among other things, due to the maintenance of interest and commission income) and the stability of its capital base showed the smallest loss of profitability. At the opposite pole was the banking sector in the Czech Republic. The study used comparative, statistical data and quartile analysis. The formulated conclusions may be useful for supervisory institutions and governments of CEE countries. A limitation of our results is that they are based on highly aggregated data and do not take into account economy-specific reasons for the erosion of bank results (in Poland, for example, these would be provisions related to the portfolio of mortgages in foreign currencies).
Keywords: COVID-19; Banking Sector; ROE; Quartile Analysis